Electrocardiographic Pattern of Typhoid Fever in Children - J. M. Ch. Pelupessy; Pieter Sangka (Indonesian Pediatric Society, 1989)
Of 87 children with typhoid fever, from age ranging in 2.5 to 14 years, 62.0% showed ECG changes. Sinus tachycardia and left ventricular hypertrophy were the two most frequent abnormalities.The majority of ECG changes occurred in the first week of admission and return to normal two weeks thereafter. There were no significant differences in the frequency of abnormal ECG pattern by sex, age, and nutritional state.